Dark Web as a Contemporary Challenge to Cyber Security - Miloshevska, Tanja (Kriminalističke teme, 2019)
Inspiration for work: This paper looks specifically at the dark net which has become notorious in the media for being a hidden part of the web where all manner of illegal activities take place. Precisely, it draws attention to the ‘black market’ of the Internet–the dark web that represents such a hidden space, being the largest deployed anonymity network. Goals of paper: This article analyzes and highlights the major roles played by the Dark Web as a market; as a communication platform; as an enabler of cybercrime; as an enabler of anonymous financial transactions and as a proxy to a surface web. Methodology/Concept: The paper is managed by looking at current literature in academic journal databases and own research in dark web. The motivation behind this literature review is to estimate the current state and development of the dark web in relation to the roles it plays and explore how the dark web enables cybercrime. Limits of the research/work: It contributes to the space of the dark web by assisting as a citation document and by suggesting a research agenda to renew study on this phenomenon and allow for better projections on how it may reveal over time and as technology expands. Results/Conclusions: Criminality on the dark web spans multiple areas and involves a wide range of criminal commodities. An effective countermeasure will therefore require a suitably coordinated, cross-cutting response, involving investigators with equally diverse expertise. This will likely require additional capacity building and training of officers not involved in computer crime. And while though this awareness may not necessarily stop national security threats from the Dark Web, it can certainly shine a spotlight on the issue and facilitate a larger conversation on how the global community can address these emerging threats. Accountability of the research: The unique nature of Dark Net markets as highly anonymous and secretive, as well as loyal and intelligent, makes them an ideal test case for the unrestrained online market-place. There is a need for a global strategy and accountability to address the abuse of the dark web and other emerging platforms for illicit trade.